Le choc de la nouvelle? Maastricht, déjà vu and EMU reform - Kevin Featherstone (London School of Economics and Political Science (LSE), European Institute, 2012)
This paper explores the extent to which current reforms of the euro-zone's governance remain encased in the constraints of the Maastricht Treaty - the narrowness of its underlying paradigm; the gaps and imbalances of its design – and the implications for the future of the euro. With a model of 'sound money, sound finances', based on the precepts of German ordo-liberalism, a vulnerability was exposed: it lacked the instruments, not only to aid, but also to police. This was exacerbated by the shallowness of public legitimation, ignored from the outset. The uncertainty, delays and division displayed by the euro-zone's response to the crisis owed much to the 'lock-in' of Maastricht. The paper includes a critical reassessment of Dyson and Featherstone (1999).
Keywords: 330